KONSEP GANTI RUGI DALAM PERBUATAN MELAWAN HUKUM DAN WANPRESTASI SERTA SISTEM PENGATURANNYA DALAM KUH PERDATA - APRIANI, TITIN (Universitas Mahasaraswati Mataram, 2021)
This research is a library research, which uses data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is to collect various ideas, theories and concepts from various literatures that focus on the process. comparison between arguments, articles or other laws. The results of the research can be concluded that regarding acts against the law are important things in the field of civil law. The application of the conception of an act against the law is often equated with the conception of breaking a promise (default). Whereas both are very different conceptions from one another, even though both originate from the agreement, namely the conception of default originating from an agreement which is born from an agreement and the conception of unlawful acts originating from an agreement born from a law.